DERAJAT KEASAMAN (pH) VINEGAR DALAM MEDIA LIMBAH FERMENTASI BIJI KAKAO AKIBAT PENAMBAHAN KONSENTRASI Acetobacter aceti DAN WAKTU INKUBASI - Kusmawati, Wiwik (El-Hayah : Jurnal Biologi, 2015)
The study was aimed to identify the degree of acidity (pH) vinegar in a medium waste fermentation of cocoa beans due to the addition of Acetobacter aceti concentration and time of incubation.This research utilised two factor, factorial design with completely randomized design (CRD). Thefirst factor is the Acetobacter aceti consentration (10%, 13%, dan 16%). The second is the time of incubation (6, 8, dan 10 day). Results were analyzed by using SPSS program version 11 personal computer, two way ANOVA and multiple comparison test with significance level of 0,05.The results of analysis of variance showed that there were differences in the degree of acidity (pH) of vinegar in a medium waste fermentation of cocoa beans due to the addition of Acetobacter aceti concentration and time of incubation. While Duncan's test results showed the treatment inoculation 13% starter Acetobacter aceti with 6 days of incubation time significantly different from the other treatments with minimal pH is 2,02. So that these results meet the standards of vinegar. From these experiment we suggested that consentration of Acetobacter aceti and incubation period has effects in the degree of acidity (pH) vinegar in fermentation waste of cacao seed medium